Piloting the Play Cycle Observation Method in 'real time': Recording children's Play Cycles in pre-school provision. (September 2021) - King, Pete; Atkins, LaDonna; Burr, Brandon
The Play Cycle Observation Method (PCOM) is an observational tool developed to focus on the process of play and has shown good reliability when watching videos of children playing. This study piloted use of the PCOM in 'real time' in a pre-school setting where 3-year-old children play. The results from two independent observers not familiar with the concept of the Play Cycle or the PCOM found good inter-rater reliability using Cohen Kappa (k) when observing play cues to form play cycles, as well as observing play cues within established play cycles. In addition, the recording of the nature of the play cues and play returns, the play frame and how the play cycle finishes (annihilation) were shown to be consistent between the two inter-rater observers. The results of this pilot study indicate the PCOM can be used as an observational tool to record the process of play by both students and practitioners working in a range of contexts including playwork, childcare, early years and statutory education. The PCOM can also be used as a teaching and training aid for trainers and lecturers.